Faktor-Faktor yang Mempengaruhi Minat Ibu Nifas terhadap SPA Nifas di Desa Sukomulyo Kecamatan Pujon Kabupaten Malang - Suriati Suriati; Siti Asiyah; Brivian Florentis Yustanta (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Spa service that done according to holistic with fuse various tradisional healthy treatment and modern that use water to give therapy effect to achieve balance between body, idea and soul, so that materialized optimal healthy condition and overcome unpleasant at postpartum.Interest in postpartum spa was influenced by various factor. There were knowledge about postpartum spa, social motive and mother need at postpartum. Those research would be where would researcher would factors that effect postpartum interest doing postpartum spa at Sukomulyo Village Pujon District. factors by knowledge, social motive, and need. The research used to approach cross. The plan research describe variable or condition what going on at one particular situation that was interest uses postpartum spa. Data was analysis in used to analysis fisher exact's that was detect effect knowledge, motive social and need to interest postpartum to do spa. The analysis result data 68,43 %. had good knowledge hits spa postpartum, has which were positive social motive much as 84,22% while respondent wanted postpartum spa much as 68,43%. Data with standard signifikansi 0,05.Give effect in respondent interest because with good knowledge one would would done spa postpartum. Also connected with that was ρ value knowledge, 0,003 ρ value social motive 0,021 ρ value need 0,017. Also norm subjektif perception somebody hits to hit belief and postpartum mother behaviour about postpartum spa. Belief and postpartum mother evaluation about consequence postpartum spa was one of the element that effect postpartum mother to do postpartum spa. After mother would give mother would feel need other will return self fitness, one of them can be done to pass postpartum spa.